China's path to the new economy an institutional approach - Richard Sanders; Chen Yang (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
As a driving force of the New Economy, the role of government in the development of high-tech sectors in China is the focus of this paper. Adopting an institutional approach, we argue that China has coped with simultaneous economic development and institutional transition within its unique 'contextual circumstances' and that gradualism and pragmatism have turned out to be the 'path dependent' solutions for China to deal most successfully with the 'churn' of transition. We argue that, with regard to China, the institutional arrangements of the Mao era (1949-76), with its features of rigid party/state governance structures and the political norm of the collective good, shaped both the evolution of the new institutional framework and the nature of the market in China-in-transition under Deng Xiaoping and Jiang Zemin in the succeeding twenty five years. We argue that the springboard for growth of the high-tech sectors in China in the latter period was the science and technology and R&D capabilities that had accumulated under Mao in which a unique 'government-industry-university' partnership was forged. China's prior institutional framework allowed government and the universities to engage in activities that went far beyond basic research and which became the early driving forces for product development and commercial adventures in the high-tech sector. On the basis of an empirical study of high-tech university spin-offs we conclude that their evolutionary process has been characterized by 'fuzzy property rights' and 'public entrepreneurship', and through these concepts, attempt an explanation of the 'path dependence' of the Chinese high-tech sector.
Keywords: 330; Technologiepolitik; Institutionelle Infrastruktur; China; New Economy